-17+4a=-4(2+a)+7

Simple and best practice solution for -17+4a=-4(2+a)+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -17+4a=-4(2+a)+7 equation:


Simplifying
-17 + 4a = -4(2 + a) + 7
-17 + 4a = (2 * -4 + a * -4) + 7
-17 + 4a = (-8 + -4a) + 7

Reorder the terms:
-17 + 4a = -8 + 7 + -4a

Combine like terms: -8 + 7 = -1
-17 + 4a = -1 + -4a

Solving
-17 + 4a = -1 + -4a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '4a' to each side of the equation.
-17 + 4a + 4a = -1 + -4a + 4a

Combine like terms: 4a + 4a = 8a
-17 + 8a = -1 + -4a + 4a

Combine like terms: -4a + 4a = 0
-17 + 8a = -1 + 0
-17 + 8a = -1

Add '17' to each side of the equation.
-17 + 17 + 8a = -1 + 17

Combine like terms: -17 + 17 = 0
0 + 8a = -1 + 17
8a = -1 + 17

Combine like terms: -1 + 17 = 16
8a = 16

Divide each side by '8'.
a = 2

Simplifying
a = 2

See similar equations:

| 192xsquared-12=0 | | 4x+9x-80=60-7x | | 30=.41x-4.28 | | 32-7k=5k-7(4+2k) | | 7x+4x-45=30-4x | | 2n-7=7 | | -15x=435 | | 25x^3-81x=0 | | 5x+6x-80=40-9x | | 8c+3-14c+36= | | 26-3n=-(8n-1) | | 0=4.9x^2+20x-100 | | 8x^2-10x=-9 | | 7(4x-9)= | | 0=4.9x^2+20x-300 | | y=4.9x^2+20x-300 | | 5x-30-2x+17=4(x-2)-3(3-2x)-(3x+44) | | 8r-26=-41+3r | | 7y-23=-11+4y | | (8x^3+5x^5-4)+(9x^4+9)-(-3x^4+7x^5+5x^2)= | | .2x+.04x=4.8 | | 2x(2x-9)(6x+5)=0 | | 2x^2-100=40 | | 2x=7+1 | | 64x^2+81= | | p(x)=x^2+7x+6 | | (2*6.5-h)*h=0.64 | | (2*6.5-h)*h= | | (-5.6x)+2.9x-3.86=-9.8 | | 7+35x=21x+11 | | 3/4x+2=1/2x-3 | | (2r-4)*4=36 |

Equations solver categories